2018
DOI: 10.1056/nejmoa1713709
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Adjuvant Chemotherapy for Stage III Colon Cancer

Abstract: Among patients with stage III colon cancer receiving adjuvant therapy with FOLFOX or CAPOX, noninferiority of 3 months of therapy, as compared with 6 months, was not confirmed in the overall population. However, in patients treated with CAPOX, 3 months of therapy was as effective as 6 months, particularly in the lower-risk subgroup. (Funded by the National Cancer Institute and others.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
777
5
21

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 804 publications
(838 citation statements)
references
References 16 publications
35
777
5
21
Order By: Relevance
“…Pharmaceutical companies are not typically interested in sponsoring trials for neglected cancers (eg, liver, brain) or for investigating de‐escalation of established cancer medicines that are no longer under patent . PHARE (described above) was funded by the French National Cancer Institute, whereas the International Duration of Evaluation of Adjuvant Therapy (IDEA) analysis of colon cancer was funded by various noncommercial grants …”
Section: Optimizing Cancer Medicine Researchmentioning
confidence: 99%
“…Pharmaceutical companies are not typically interested in sponsoring trials for neglected cancers (eg, liver, brain) or for investigating de‐escalation of established cancer medicines that are no longer under patent . PHARE (described above) was funded by the French National Cancer Institute, whereas the International Duration of Evaluation of Adjuvant Therapy (IDEA) analysis of colon cancer was funded by various noncommercial grants …”
Section: Optimizing Cancer Medicine Researchmentioning
confidence: 99%
“…1 TNM staging system is an important guide for physicians regarding treatment and prognosis. 3,4 The current staging method is suboptimal due to the variation in outcomes that exist among patient in the same stage. Adjuvant chemotherapy provides a survival benefit in patients with Stage III disease, and possibly in those with high-risk Stage II colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Given the cumulative neurotoxicity associated with oxaliplatin exposure, the International Duration Evaluation of Adjuvant Therapy (IDEA) collaboration conducted a prospective pooled analysis and showed that 3 months of adjuvant therapy appeared to be sufficient in a lower‐risk group (defined as patients with T1, T2, or T3/N1 disease), especially when the capecitabine and oxaliplatin combination was chosen. In a higher‐risk group (patients with T4, N2, or both), 6 months of adjuvant therapy may be needed, particularly when the fluorouracil and oxaliplatin combination was the chosen regimen (Grothey et al , ). Notably, our study showed that patient survival was heterogeneous even within the high‐ or low‐risk stage II/III groups; that is, patients with high‐risk stage II and low‐ and high‐risk stage III disease could be further stratified by the cirScore into subsets with distinct outcomes, suggesting a room for tailoring treatment strategies and avoiding overtreatment or undertreatment in selected patients.…”
Section: Discussionmentioning
confidence: 99%